(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Acute cholecystitis and some conditions associated with gallbladder stones, such as depressed common bile duct stones, cholangitis, and biliary pancreatitis, are common diseases in daily practice. Early cholecystectomy or placement of a drain, a procedure with delayed cholecystectomy, is the current standard of care based on published clinical guidelines. Chronic diffuse liver disease is not only a state of chronic liver dysfunction, but also has systemic effects in patients. In individuals with chronic diffuse liver disease, several predisposing factors, including changes in bile acid composition, increased bile nucleation, and decreased gallbladder motility, contribute to the formation of gallstones and the possibility of symptomatic cholelithiasis, which is an indication for surgical treatment. In addition to these predisposing factors for gallstone disease, the systemic effects and local anatomical consequences associated with chronic diffuse liver disease, in particular liver cirrhosis, lead to anesthetic risks and perioperative complications in patients with liver cirrhosis. Therefore, the treatment of the aforementioned biliary conditions in patients with liver cirrhosis has become a challenging task.